Role of SWI in Identifying Microhemorrhages in Mild Traumatic Brain Injury - Kalytis, Lukas; Dementavičienė, Jūratė (Neurologijos seminarai, 2024)
Mild traumatic brain injury (mTBI) is a prevalent neurological condition which can result in long-term cognitive and functional impairments, often linked to microhemorrhages and subtle bleeding that may not be visible when using the conventional imaging techniques, such as CT or standard MRI. Susceptibility Weighted Imaging (SWI) has emerged as a valuable tool for detecting these subtle abnormalities due to its enhanced sensitivity to magnetic susceptibility differences. This literature review explores the role of SWI in identifying microhemorrhages associated with mTBI. It examines the advantages of SWI over the traditional imaging modalities, highlighting its capability to detect microbleeds that are crucial for accurate prognosis of mTBI. Furthermore, the review discusses the integration of SWI with other advanced imaging techniques, such as Quantitative Susceptibility Mapping (QSM), to improve diagnostic accuracy and monitor imaging changes over time.
Keywords: Susceptibility weighted imaging (SWI); mild traumatic brain injury (mTBI); microhemorrhages cerebral microbleeds (CMBs); raumatic microbleeds (TMBs); quantitative susceptibility mapping (QSM); post-concussive syndrome (PPCS)